Juvenile nursery colonization patterns for the European flounder (Platichthys flesus): A latitudinal approach - Martinho, Filipe (2013)
In this work, we analysed the latitudinal trends in the nursery habitat colonization processes of the European flounder (Platichthys flesus). This was accomplished by estimating the duration of the pelagic and metamorphic stages, aswell as the duration of the spawning period, in several nursery areas across its geographical distribution range in the European Atlantic Coast: Mondego estuary (Portugal), Vilaine estuary (France), Slack estuary (France), Wadden Sea (Netherlands) and the Sørfjord (Norway). All juvenile flounders were captured with beam trawls in June/July 2010, and otolith microstructure was used to determine the duration of each stage by means of daily growth increments. The pelagic and metamorphic stages were longer at the middle of the distribution range, and lasted in total up to two months after hatching. The spawning period occurred between mid- January and early-July over the species' distribution range, with a time lapse of nearly two months between the Mondego estuary and the Sørfjord, as a consequence of warmer water temperature earlier in the season in southern areas. In general, total length of the captured fish showed a latitudinal cline between the northernmost and southernmost sampling sites, with higher values at the middle of the distribution range. The results also suggested the existence of a countergradient growth compensation mechanism in the northernmost populations. Apart from temperature, which sets the general metabolic pace of organisms, differences between siteswere also related with local features, such as the extension of the continental platform and adaptations to transport and retention mechanisms.